2022
DOI: 10.3390/foods11111566
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scenario Simulation Analysis of Grain Production and Demand in China during the Peak Population Period

Abstract: The transformation of dietary structure brought about by economic development in populous countries is expected to trigger an increase in grain demand, which will put enormous pressure on the grain supply in these nations and even globally. We simulated nine demand scenarios for 2020–2050 based on China’s dataset for 15 kinds of grains from 1961–2018. The results show that the maximum difference between the predicted grain demand is 323.8 Mt, equal to the total grain consumption of approximately 600 million Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Globally, food crop production can only fulfil the demand for the less than one-third of the population [ 1 ]. Furthermore, forces originating from population growth and economic development have stimulated food needs, putting increasing pressure on food production [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, food crop production can only fulfil the demand for the less than one-third of the population [ 1 ]. Furthermore, forces originating from population growth and economic development have stimulated food needs, putting increasing pressure on food production [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a significant factor impacting GD, food waste in the consumption stage was often ignored due to poor data. Many have argued that food waste should be included in prediction of future GD [52,56,57]. In our Equations ( 4), ( 6) and (10), we account for this waste in consumption stage through the parameter C t j .…”
Section: Grain Consumption In Chinamentioning
confidence: 99%
“…According to the report on Nutrition and Chronic Diseases in China 2020 [ 18 ], the overweight and obesity rate of Chinese adult residents exceeds 50%, while it is nearly 20% in children and adolescents aged 6–17, and 10% in children under 6 years old. Studies have shown that dietary obesity caused by the imbalance between energy intake and physical activity is an important reason for the increasing incidence of obesity and chronic diseases in China [ 19 , 20 ]. In this context, the relationship between the change in China’s population structure and the change in residents’ energy intake has attracted more and more attention from the government and academia.…”
Section: Introductionmentioning
confidence: 99%